Dipper pattern in arterial hypertension: is there a correlation with ageing?. (11th May 2021) - Neto, V
Abstract: Funding Acknowledgements: Type of funding sources: None. Dipper pattern in arterial hypertension: is there a correlation with aging? Background: Systemic arterial hypertension is an important cardiovascular risk factor. Non-dipper hypertension is associated with increased cardiovascular morbidity and mortality. Purpose: Study the effect of aging in the dipper pattern, in patients submitted at 24-Hour Ambulatory Blood Pressure Monitoring. Methods: Retrospective study based on patients submitted at 24-Hour Ambulatory Blood Pressure Monitoring on the first trimester of 2020. Patients were divided into categories based on percentage of nighttime blood pressure drop: 0% Reverse Dipper, 0-10% Non-Dipper, 10-20% Dipper e >20% Extreme Dipper. The sample was dived into two groups: group A (GA) with age between 18- and 60-years vs group B (GB) with age between 60- and 90-years. Results: This study included 91 hypertensive patients, whom 46.2% were male and with a mean age of 56 ± 15 years. GA represented 60.4% of study sample, whom 43.6% were male and with a mean age of 46 ± 10 years. In the group B, 50% were male with a mean age of 71 ± 6 years. GB patients had more history of diabetes (7.8% vs 26.5%, p = 0.022). No significant difference was found between the two groups in history of kidney chronic disease, obesity or sleep apnea syndrome. In terms of medical treatment, GB had more prescription of loop diuretics (3.9% vs 22.9%, p = 0.010) and angiotensin-converting enzyme (ACE) inhibitors (58.8% vs 88.6%, p = 0.028). No significant differences were found in the prescription of other hypertension therapies or the use of drug combinations. No significant difference was found in the number of Dippers in both groups (63.6% vs 58.3%, p = 0.386). GB had more reverse dippers (1.8% vs 16.7%, p = 0.014). GA had more extreme dippers (12.7% vs 2.8%, p = 0.024). Conclusion: There is no difference in the rate of dipper pattern accordingly to age. The prevalence of reverse dippers in older patients was superior, leading to increased risk of cardiovascular events in this group. The younger group had more prevalence of extreme dippers, which, by some authors, can lead to increased risk of a silent cerebrovascular event.